Host defense peptide‐derived privileged scaffolds for anti‐infective drug discovery. (12th January 2017) - Nigro, Ersilia; Colavita, Irene; Sarnataro, Daniela; Scudiero, Olga; Daniele, Aurora; Salvatore, Francesco; Pessi, Antonello
Abstract : 'Privileged scaffolds' are molecular frameworks which have been successfully exploited for small molecule drug discovery. Peptide privileged scaffolds, featuring a strictly conserved multiple‐disulfide framework and high variability in the rest of the sequence, display a broad range of biological effects, including antimicrobial and antiviral activity. Unlike small molecules, however, the cost of manufacturing these peptides is high, and their synthesis challenging. We previously described a simplified privileged scaffold corresponding to the γ‐core of human β‐defensin‐3 (HBD3). The γ‐core is a common structural signature found in virtually all host defense peptides (HDPs) stabilized by multiple disulfides, and we showed that for HBD3, it represents the evolutionary starting point of the full‐length molecule and, thus, is itself a primordial HDP. Accordingly, we showed that the peptide folded rapidly and was stable in human serum, and displayed many of the biological activities of HBD3. We report here that in addition to the previously reported antibacterial activity on planktonic bacteria, the γ‐core peptide is active against biofilm formation and maturation. We also show that it is readily cell penetrant, like HBD3, although with a different mechanism, which is independent from CD98. Overall, the potency of the single‐disulfide, 23‐amino acid γ‐core is comparable with the full‐length peptide across the whole spectrum of examined properties, and the peptide is not toxic to human cells. The HBD3 γ‐core peptide may therefore represent the first example of an economically viable lead peptide derived from a HDP privileged scaffold. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Peptide privileged scaffolds with a multiple‐disulfide framework display a broad range of biological effects, but with challenging synthesis and high manufacturing cost. Simplified privileged scaffolds are found in the common structural signature of host defense peptides (HDPs), named the γ‐core. The single‐disulfide, 23‐amino acid γ‐core of human β‐defensin‐3 is stable in human serum and displays many of the biological activities of the full‐length peptide, representing an economically viable lead peptide derived from a HDP privileged scaffold.